An Investigation of Medical School Curriculum in Kerman University of Medical Sciences Iran Based on the CIPP Model - Sedigheh Khodabandeh; Parisa Rostambeig; Sakineh Sabzevari; Esmat Nouhi (Kerman University of Medical Sciences, 2016)
Background & Objective: In order to improve the quality of higher education programs and make them dynamic quantitative and qualitative evaluations and assessments are required In this study the context input process and product (CIPP) evaluation model was used to evaluate the School of Medicine at Kerman University of Medical Sciences Iran in 2014 Methods: The evaluation of this school based on the CIPP model consisted of the 4 components of context input process and output The sample included 69 students 20 professors and 12 postgraduates A researcher made questionnaire was used to collect data The scores of 015 1535 and 355 were considered as representing poor conditions relatively favorable conditions and favorable conditions respectively Data were analyzed using SPSS software and descriptive and inferential statistics (ttest) Results: From the perspective of the participants of the research the status of context input process and output and in general the School of Medicine was favorable and the output of the school was relatively favorable There was a significant difference between the students and professors point of views in terms of the context process and outcome of the school (P < 005) The students ranked the context as favorable while the professors ranked input process and output of the school as favorable Conclusion: The results of the final evaluation revealed that the condition of this school is favorable To achieve a highly favorable condition it is suggested that college and university authorities attempt to strengthen important factors such as revision of curriculum content and training professors on teaching methods evaluation and communication skills